Short-term HRV in young adults for momentary assessment of acute mental stress. (March 2020) - Chen, Yingyue; Zhang, Liping; Zhang, Bei; Zhan, Chang'an A.
Highlights: Block design eliciting "low-high-low-high" acute mental stress variation profile. Systematical analysis of the reliability and sensitivity of the prominent HRV metrics (N = 42) for assessing acute stress. About one third of the HRV metrics robustly track the momentary change of acute mental stress. About half of the HRV metrics respectively hold relative and absolute reliability, while only one fifth hold both. Abstract: Mental stress has become a major health threat in our society and its continuous monitoring and timely intervention is key to stress management. Heart rate variability (HRV) has been considered as a potential candidate for ecological momentary assessment of acute mental stress, and growing number of HRV metrics have been developed. However, inconsistency of findings in prior studies necessitates further investigation on what are the appropriate metrics in tracking the momentary variation of mental stress. This study employs a block design inducing low-high-low-high stress variation profile to test the feasibility of a broad range of HRV metrics for measuring the minute-scale stress variation elicited by the commonly used mental arithmetic tasks. After extracting the RR interval series, 42 HRV metrics have been examined in absolute reliability, relative reliability, and the statistical significance in differentiating the low and high stress levels. Among these metrics, 22 show absolute reliability, 21 show relative reliability, and 13 differentiate the low and high stress levels consistently across all four pairs of comparison. Venn's diagram analysis resulted eight metrics hold both absolute and relative reliability, whereas those metrics robustly differentiating high and low stress levels hold either absolute (3/13) or relative (10/13) reliability. Our results show that, although not all HRV metrics hold both absolute and relative reliability, about one third of the examined HRV metrics can effectively track the variations of mental stress. These findings suggest the importance of HRV metrics selection when applied for monitoring acute mental stress.